Oxidative Stress-Induced Axon Fragmentation Is a Consequence of Reduced Axonal Transport in Hereditary Spastic Paraplegia SPAST Patient Neurons - Wali, Gautam; Liyanage, Erandhi; Blair, Nicholas F.; Sutharsan, Ratneswary; Park, Jin-Sung; Mackay-Sim, Alan; Sue, Carolyn M. (Frontiers in Neuroscience, 2020)
Hereditary Spastic Paraplegia (HSP) is a group of inherited disorders characterised by progressive spasticity and paralysis of the lower limbs. Autosomal dominant mutations in SPAST gene account for ~40% of adult-onset patients. We have previously shown that SPAST patient cells have reduced organelle transport and are therefore more sensitive to oxidative stress. To test whether these effects are present in neuronal cells we first generated eleven iPS cell lines from fibroblasts of three healthy controls and three HSP patients with different SPAST mutations. These cells were differentiated into FOXG1-positive forebrain neurons and then evaluated for multiple aspects of axonal transport and fragmentation. Patient neurons exhibited reduced levels of SPAST encoded spastin, as well as a range of axonal deficits, including reduced levels of stabilised microtubules, lower peroxisome transport speed as a consequence of reduced microtubule-dependent transport, reduced number of peroxisomes and higher density of axon swellings. Patient axons fragmented significantly more than controls following hydrogen peroxide exposure, suggesting for the first time that the SPAST patient axons are more sensitive than controls to the deleterious effects of oxidative stress. Treatment of patient neurons with tubulin-binding drugs epothilone D and noscapine rescued axon peroxisome transport and protected them against axon fragmentation induced by oxidative stress, showing that SPAST patient axons are vulnerable to oxidative stress-induced degeneration as a consequence of reduced axonal transport.